Synthesis of 3-carbethoxy-4(3’-chloro-4’-hydroxy) phenyl-but-3-en-2-one and its cytotoxicity evaluation against cancer cell carrying mutant p53 - Julianus, Jeffry; Mustofa; Jumina (Faculty of Medicine, Public Health, and Nursing Universitas Gadjah Mada and Indonesian Pharmacologist Association or Ikatan Farmakologi Indonesia (IKAFARI), 2021)
Overexpression of mutant p53 in cancer cell inactivates the p53 pathways to execute apoptosis and cell cycle arrest. This study aimed to synthesize new kardiena derivative compound, 3-carbethoxy-4(3’-chloro-4’-hydroxy)phenyl-but-3-en-2-one, to reactivate the p53 pathways to execute apoptosis and cell cycle arrest. Characterization of the synthetic compound employing melting point, IR, EI-MS, 1H-NMR, and 13C-NMR spectra revealed 3-carbethoxy-4(3’-chloro-4’-hydroxy)phenyl-but-3-en-2-one was successfully synthesized from 3-chloro-4-hydroxybenzaldehyde and ethyl acetoacetate using dimethylamine as a catalyst. This compound had antiproliferative activity against the WiDr cells which carried mutant p53. Its antiproliferative activity was better than 5’-FU as a reference standard to treat colon cancer. Increasing WiDr cell accumulation in the G2-M phase, the active form of caspase-3, and inducing apoptosis demonstrated the ability of 3-carbethoxy-4(3’-chloro-4’-hydroxy)phenyl-but-3-en-2-one to reactivate p53 pathways to execute apoptosis and cell cycle arrest in cancer cells carrying mutant p53.